Penyelesaian Sengketa di Segmen Noel Besi – Citrana antara Indoneia dan Timor Leste - Dewa Gede Sudika Mangku (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2019)
In Kupang District there is an unresolved segment, namely Noel Besi- Citrana, which is a disputed land along a river or delta starting from Co. 1745-6475 to Co. 1870-6770. The dispute area is located in Kupang Regency, with an area of ± 1,069 Ha, originating from the land dispute. When East Timor was still joining NKRI, the Noel Besi-Citrana area was the border area of Kupang Regency (NTT) and Ambeno Regency (Timor Leste region). The area of dispute is Naktuka which is located between the Noel Besi River and the Nono Noemna River. Based on the Provisional Agreement in 2005 Article 6 point (b) which implies that local communities in this case the customary community / customary leaders are given space to be involved in the process of resolving disputes that occur at the borders of the two countries by promoting peaceful and nonviolent means in accordance with Article 8 Provisional Agreement in 2005. Whereas the people who inhabit West Timor (Indonesia) and the people who inhabit East Timor (Timor Leste) have the same socio-cultural background, it can be ensured that the customary law arrangements in force in these two community groups also the same. However, this actually becomes an obstacle when the state takes the primary role, regardless of the Customary Figures who have the potential to determine the peaceful settlement of national borders in a family atmosphere..